Perayaan Imlek EtnIs Tionghoa: Menakar Implikasi Psiko-sosiologis Perayaan Imlek bagi Komunitas Muslim di Lasem Rembang - Hasyim Hasanah (LP2M IAIN kUDUS, 2014)
abstract CHINESE NEW YEAR CELEBRATION OF ETHNIC TIONGHOA (TAKE THE NECESSARY PSYCHOSOCIOLOGICAL IMPLICATIONS OF CHINESE NEW YEAR CELEBRATIONS FOR THE MUSLIM COMMUNITY IN LASEM REMBANG). Ethnic Tionghoa or better known as Chinese people till now it is the minorities in Indonesia. But the presence of ethnic Tionghwa in religious social relations in the community gives its own color, especially in generating new forms of culture which is more unique, more sacred and, have a value of local cultural reinforcement. One form of colored cultural communities is the existence of Chinese new year celebration, which is socially it gave birth to a new form of humanitarian relationship pattern, it is a social solidarity for other communities. This study attempts to describe the psychological implications of Chinese new year celebration of ethnic Tionghwa for the Moslem community in Lasem Rembang. To get a thorough description, this study uses descriptive method with psychophenomenological approach. The results of this study mentions that the celebration of the Chinese new year ethnic tionghwa positively gave psycho-sociological implications for the Moslem community through the formation of a viable social values in the form of pro social and gave rise to a harmonious social solidarity. Besides, psychologically the existence of Chinese new year celebration is capable of creating psychological dynamics in the form of a tolerance attitude of, mutual trust, and respect between the Moslem community and ethnic Tionghwa in Lasem Rembang.